Religious Ritual Commercialization Effect on Tourists Religiosity – A Systematic Review of the Literature From the Last Two Decades (2000-2020) - Aksamawanti, Aksamawanti; Ridwan,; Nordin, Shah Rul Anuar (Advances in Humanities and Contemporary Studies, 2024)
This paper presents the results of a systematic review of research that have studied the links between religious ritual commercialization and religiosity of tourists from 2000 to 2020. The results only found eight research representing only four religious ritual destination, one of them determined by the researcher.  The findings suggest that the existing knowledge of the impact of the religious ritual commercialization and tourists religiosity has some limited views. Further tourism studies need to be undertaken in the following areas: quantitative research on the relationships between multiple form of religious tourist (pilgrim vs usual tourist) and religiosity; effects of ritual participation; effects of pilgrim vs non-pilgrimage ritual on religiosity, Islamic rituals effects on religiosity of the tourists/pilgrims, effects of rites tourism on proselytation of tourists, effects of rites tourism on different faiths of tourists, and effects of rituals on tourist religiosity based on their initial motives.